Scribal revision: a post-Qumran perspective on the formation of Jeremiah - Ghormley, Justus Theodore (Textus, 2018)
This article describes the presence of three different degrees of scribal revision in Jeremiah: (1) multidimensional revision—the revision of multiple aspects of a text in a single moment by one scribe (such as relocating the Oracles Against the Nations and the addition of new headings); (2) single-dimensional revision—the revision of one aspect of a text (such as the addition of new headings by itself) again by one scribe in one moment; and, (3) incremental revision—the ongoing, piecemeal revision of one aspect of a text by an unknown number of scribes over a longer period of time. This article offers criteria for distinguishing these degrees of revision and applies the criteria to two categories of scribal expansion in Jeremiah: the insertion of names and titles and the addition of new headings. It concludes that these features took shape through a combination of all three degrees of revision.